The Influence of Entrepreneurial Orientation, Product Innovation, and Strategic Managerial Capabilities on Business Sustainability - Sulistyowati, Ari (Dinasti Research, 2025)
The purpose of this study is to develop hypotheses related to factors that influence business sustainability, especially in MSMEs in Indonesia. The writing technique used in this literature review study is Comparative Analysis. The data collection technique is to use literature studies or review previous relevant articles. The data used in this descriptive qualitative approach came from previous studies relevant to this research and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Q2-Q4 Emerald, Elsevier, Sage, Web of Science, Sinta 2-5 Journal, DOAJ, EBSCO, Google Scholar, and digital reference books. The results of the literature review with MSME actors in Indonesia as the object are as follows: 1) Entrepreneurial orientation affects business sustainability, 2) Product innovation affects business sustainability, and 3) Strategic managerial capabilities affect business sustainability. This study contributes to the understanding of factors that influence the sustainability of MSME businesses in Indonesia, with a focus on factors such as entrepreneurial orientation, product innovation, and strategic managerial capabilities. This study adds new insights into other factors that influence entrepreneurial orientation, product innovation, and strategic managerial capabilities, especially in MSMEs in Indonesia. Thus, it can be used as a reference in future literature.